Polymorphisms in NEIL-2, APE-1, CYP2E1 and MDM2 Genes are Independent Predictors of Gastric Cancer Risk in a Northern Jiangsu Population (China) - Elingarami, Sauli; Liu, Hongna; Kalinjuma, Aneth Vedastus; Hu, Weiyue; Li, Song; He, Nongyue (Journal of nanoscience and nanotechnology, 2015)
China is one of the countries with the highest incidence of gastric cancer, and accounts for over 40% of all new gastric cancer cases in the world. Genetic factors as well as environmental factors play a role in development of gastric cancer. To investigate the independent roles of single nucleotide polymorphisms (SNPs) in base excision repair (BER) genes (APE1 and NEIL2), carcinogen metabolism gene (CYP2E1) and tumor suppressor pathway gene (MDM2) for gastric cancer susceptibility in a Chinese population, we conducted a hospital based case-control study to evaluate the potential association between these polymorphisms and susceptibility to gastric cancer in a Northern Jiangsu population. We also associated the NEIL-2 mRNA expression with the studied NEIL2 SNP genotypes to assess whether the genotypes have influence on the NEIL2 mRNA (hence protein) expression. Five SNPs, APE 1 (rs2275008), NEIL 2 (rs804270), MDM2 (rs2279744), and CYP 2E1 (rs2480256 and rs2031920), were genotyped by TaqMan assays in 105 gastric cancer cases and 118 controls. Genotype frequency distribution showed that the APE 1 SNP (rs2275008), NEIL 2 SNP (rs804270), MDM2 SNP (rs2279744), and CYP 2E1 SNP (rs2031920) had more mutant alleles in gastric cancer cases than controls (76.19, 68.57, 54.29, and 43.81%, respectively), while CYP 2E1 SNP (rs2480256) had large percentage of both alleles (43.81%). Risk analysis revealed that there was increased risk for gastric cancer in subjects with mutant alleles in APE 1 (rs2275008: OR 5.49, 95% CI = 2.6-5.7, p <.0001), NEIL 2 (rs804270: OR 2.3, 95% CI = 1.22-4.3, p=0.01), MDM2 (rs2279744: OR 14.65, 95% CI = 5.63-8.15, p < .0001), and CYP 2E1 (rs2031920: OR 8.385, 95% CI = 3.2-5.3, p < .0001) SNPs. Moreover, the NEIL2 mRNA expression analysis showed that there was significant differential expression of NEIL2 mRNA among the randomly tested NEIL2 genotypes (p = 0.005), with low expression seen in variant genotypes than in other genotypes. In conclusion, variant alleles in the NEIL2 (rs804270), APE1 (rs2275008), CYP2E1 (rs2031920) and MDM2 (rs2279744) SNPs may independently influence susceptibility to gastric cancer in a Northern Jiangsu Chinese population. The genotypes may also independently influence their respective gene mRNA expression, as seen in our study, where there was differential expression of the NEIL2 mRNA among the genotypes, with low NEIL2 mRNA expression seen in the variant genotype.